A Facile Strategy to Support Palladium Nanoparticles on Carbon Nanotubes, Employing Polyvinylpyrrolidone as a Surface Modifier. Issue 9 (5th March 2014) - Cardoso, Mariana B. T.; Lewis, Edward; Castro, Pollyana S.; Dantas, Luiza M. F.; De Oliveira, Caio C. S.; Bertotti, Mauro; Haigh, Sarah J.; Camargo, Pedro H. C.
Abstract: This paper describes the development of a facile and environmentally friendly strategy for supporting palladium nanoparticles (Pd NPs) on multiwalled carbon nanotubes (MWCNTs) with ethanol as the solvent/reducing agent, potassium tetrachloropalladate(II) (K2 PdCl4 ) as the Pd precursor, and polyvinylpyrrolidone (PVP) as the surface modifier. More specifically, our approach was based on the nonbonding interaction between MWCNTs and PVP, which is a cheap, nontoxic, and commercial polymer. As PVP can serve not only as a surface modifier but also as a stabilizing agent for Pd NPs, the utilization of additional functionalization steps, reducing agents, and stabilizers was not required to achieve uniform Pd deposition over the MWCNTs. Our results demonstrate that Pd NPs below 5 nm in diameter can be directly supported on MWCNTs by this route. Also, sequential Pd‐reduction steps can be employed to improve the coverage of Pd NPs at the MWCNT surfaces, although this can also lead to the formation of larger Pd particles or aggregates. The electrocatalytic activity for ethanol oxidation was investigated as a function of the composition and structure of the materials produced, in which MWCNTs decorated with Pd NPs of smaller sizes and lower coverages displayed the highest activities. The results described herein suggest that our approach may serve as a simple platform for the synthesis of MWCNTs decorated with metal NPs with well‐defined morphologies and uniform dispersion for electrochemical and catalytic applications. Abstract : The nonbonding interaction between polyvinylpyrrolidone (PVP) and multiwalled carbon nanotubes (MWCNTs) was employed to achieve deposition of palladium nanoparticles less than 5 nm in size over the surface of the MWCNTs; with ethanol as the solvent/reducing agent, potassium tetrachloropalladate(II) as the precursor, and PVP as the surface modifier.